Sex pheromone of the pink grass worm Tmetolophota atristriga (Walker) - Mitchell, V.J.; Manning, L.M.; El-Sayed, A.M. (New Zealand Plant Protection, 2008)
The New Zealand native moth Tmetolophota atristriga (Walker) (Lepidoptera Noctuidae) is a background pest defoliating pasture This project identified the pheromone components of the female pink grass worm that could be used to trap male moths in a control or monitoring programme Extraction of the sex pheromone gland of virgin female moths and GCMS analysis has identified several compounds in the sex pheromone gland two monounsaturated compounds cis11hexadecenal (Z1116Ald) and cis11hexadecyl acetate (Z1116Ac) and three saturated compounds hexadecan1ol (16OH) hexadecyl acetate (16Ac) and octadecan1ol (18OH) and triene hydrocarbon (ZZZ)369tricosatriene (Z3Z6Z923Hy) A field trapping experiment was conducted using binary blends of the two main compounds Z1116Ald and Z1116Ac at five different ratios (ie 1000 7525 5050 2575 and 0100) The highest catch was obtained at ratio 2575 of Z1116AldZ1116Ac; males were also caught at the 5050 ratio No catches were recorded with any other ratio tested A dose response experiment was conducted testing five loadings of the optimum binary (2575 ratio) mixture (01 1 10 100 and 1000 mg loading) and males were caught only at 01 and 1 mg loadings In a field trapping experiment conducted late in the season (2008) using the three additional minor compounds only the addition of Z3Z6Z923Hy to the binary mixture significantly enhanced male attraction